Pengaruh Skeptisime Profesional, Efikasi Diri, Iklim Etika terhadap Penilaian Etika Auditor Internal di Sektor Publik Dili, Timor-Leste - Clara Andrade Pereira; Djoko Susanto; Baldric Siregar (AKUNTANSI 45, 2026)
This study examines the effect of professional skepticism, self-efficacy, and ethical climate on the ethical judgment of internal auditors in the public sector of Dili, Timor-Leste. A quantitative research approach was employed, utilizing primary data collected through hard-copy questionnaires and Google Forms. The data were analyzed using SPSS version 25. The sample consisted of 60 internal auditors working in several public sector offices. The results indicate that professional skepticism and self-efficacy do not have a significant positive effect on the ethical judgment of internal auditors. In contrast, ethical climate has a significant effect on ethical judgment. These findings emphasize that the organizational ethical climate is a key determinant in shaping the ethical judgment of internal auditors. Therefore, strengthening ethical judgment should not rely solely on individual development but must also involve the establishment of an ethical organizational environment. This demonstrates the need for public organizations to systematically build a strong ethical culture, including through internal policies, regular ethics training, and oversight mechanisms. Future research could explore additional variables such as ethical leadership or job stress that may influence internal auditors’ ethical judgments.